An effective Method For 3D Modelling of Urban Areas from Aerial Images and LiDAR data - M. Pepe; D. Costantino; V. S. Alfio; A. Grimaldi (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The aim of the paper is to identify a suitable methodology for the construction of 3D City Models (3DCM) from geospatial data. Recently, the use of hybrid sensors i.e. nadiral and oblique cameras supplemented by Light Detection And Ranging (LiDAR) sensors equipped on an aerial platform, are becoming useful instrumentation for mapping urban areas. In fact, the manuscript shows the use of such instrumentation for the production of a 3D City Model processed in the City Engine environment, starting from a geomatic dataset composed of a point cloud and a series of images covering a portion of the historic centre of Bordeaux (France). The results show the quality of the 3D models in LOD3, generated on the study area, in terms of architectural details, textures and semantic contributions.